Tinjauan Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf Terhadap Sertifikasi Wakaf Di Kecamatan Kepung Kabupaten Kediri Jawa Timur - Furotul Khasanah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
A lot of endowments in Kepung have not been certified yet, so there is worry about the existence of legal problems. Education institution and religion service endowments have not had certificate yet, so they have a chance to be a dispute. By the issuing of the law number 41 in 2004 about endowment, it is hoped to be able to optimize, increase the endowment institution and also resolve the problems of the endowments. The research problems are as follows: (1) how is the implementation of the law number 41 in 2004 about endowments?, (2) how is the review of the law number 41 in 2004 about endowments to endowments certification in Kepung, Kediri, East Java? and (3) how is the effect of endowments certification in Kepung, Kediri, East Java? To answer these problems, the writer used qualitative research type that refers to the legal norm contained in the laws and regulations. This research used method of the law number 41 in 2004 about endowments approach, which is, emphasized on the using of secondary and tertiary data. From the result of the research about realization of endowments based on the law number 41 in 2004 about endowments in Kepung, Kediri, East Java, there are a lot of waqif who directly give their endowments to nadzir without strong proof of acceptance.According to review of the law number 41 in 2004 about endowments, the reason of people in Kepung, Kediri, East Java did not register their endowments is not appropriate to the law number 41 in 2004 about endowments because every endowment should be registered.